Implications for Social Science of the Analysis of Online Scams and Pedophilia in Ecuador (Revista Rupturas, 2024)
The objective of this paper is to analyze the implications for the social sciences of online crimes, specifically fraud and pedophilia in Ecuador. The methodology used is justified in the conception of systematized reviews, using the analytical framework of systematized reviews in Human and Social Sciences. Databases such as Google Scholar, SCOPUS, Web of Science (WOS), Scientific Electronic Library Online (Scielo), among others, were used. The conclusions point to the need to increase research on these crimes from the social sciences, the application of the phenomenological approach, the investigation of myths and beliefs about these phenomena, the promotion of public policies and the promotion of interdisciplinarity with other behavioral sciences.
Keywords: Social sciences; cybercrime; child abuse; Social problems